Las dos Españas : "en memoria de Carpo" / [Teófilo Magdaleno Fuentes ; prólogo de Juan Carlos Rodríguez Ibarra] - Rodríguez Ibarra, Juan Carlos (1948-); Magdaleno Fuentes, Teófilo
En port.: Una vida, un hombre, un ideal